TECHNOLOGIES FOR DEVELOPING METHODICAL COMPETENCE OF FUTURE TEACHERS (Academicia Globe: Inderscience Research, 2023)
In this article, the professional competence of teachers, the procedure for using technologies, it is necessary to develop the procedure for the correct use of the forms of teaching students in the current modernized educational environment, and scientists and experts from all over the world have studied the issue of the approach from the point of view of pedagogical professional competence. scientific discussions and debates about the competence system of pedagogy, practical and theoretical preparation, the professional competence of a pedagogue, the management of personality formation, which has a managerial and formative nature, requires competence.